2020
DOI: 10.1186/s13071-020-04378-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Aedes aegypti household pupal persistence in longitudinal entomological household surveys in urban and rural Kenya

Abstract: Background Aedes aegypti is an efficient vector of several arboviruses of public health importance, including Zika and dengue. Currently vector management is the only available avenue for disease control. Development of efficient vector control strategies requires a thorough understanding of vector ecology. In this study, we identified households that are consistently productive for Ae. aegypti pupae and determined the ecological and socio-demographic factors associated with the persistence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Typically, there are local areas where mosquitoes are abundant, interspersed with other areas where numbers are lower at fine spatial scales [ 13 ]. Local high-density areas may be identifiable through specific environmental factors to some extent (e.g., [ 4 , 14 , 15 , 16 ]). Trap catches can be relatively stable across time in some areas [ 17 ], but this is not always the case with high mosquito counts for a period in one area being replaced by other local areas even within the same village or suburb.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, there are local areas where mosquitoes are abundant, interspersed with other areas where numbers are lower at fine spatial scales [ 13 ]. Local high-density areas may be identifiable through specific environmental factors to some extent (e.g., [ 4 , 14 , 15 , 16 ]). Trap catches can be relatively stable across time in some areas [ 17 ], but this is not always the case with high mosquito counts for a period in one area being replaced by other local areas even within the same village or suburb.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study conducted in an urban setting in Zanzibar found that the presence of vegetation was significantly associated with the presence of immature stages of Aedes aegypti [ 52 ]. Another study conducted in both rural and urban Kenyan setting also reported the strongest risk factor for Aedes pupa abundance were the presence of bushes, tall around the houses [ 53 ]. Thus, the combined effect of rains and more dense vegetation cover may be the probable reason for the significant increase in Aedes mosquitoes’ abundance and thus exposure to Aedes mosquito bites in Oria village, in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it can be saved for special studies or used twice in each locality, once during the wet season and once during the dry season, to identify the most productive containers. For practical purposes, the Pupal index has been the most widely used strategy [84,86]. The basis for making the greatest use of a few resources can be laid by identifying the classes of containers in the neighborhood that have the highest rates of adult emergence.…”
Section: Entomological Surveillancementioning
confidence: 99%
“…Put every pupa in a vial with a label. Large containers provide a great challenge in pupal/ demographic surveys, as it is difficult to identify the precise number of pupae in them [86,90,91].…”
Section: Entomological Surveillancementioning
confidence: 99%